POSSIBILITIES OF INCREASING THE RELIABILITY BY METHODS OF SOFTWARE AND TIME REDUNDANCY - Siroky, Peter; Hartansky, Rene; Petrilak, Jan (International Journal of Computing, 2014)
This paper includes some possibilities how to solve problems with the improvement of systems reliability on the field where traditional methods of EMC are not sufficient. Two basic types of methods will be introduced. First, methods of software redundancy and second methods of time redundancy.